One Man Initiative: Kathmandu’s Kamal Pokhari (Lotus Pond) resurrected - Thanju, Jeewan Prasad (Hydro Nepal: Journal of Water, Energy and Environment, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Hydro Nepal: Journal of Water, Energy and Environment Issue No. 3, January, 2008 Page 53-54